2015
DOI: 10.1016/j.celrep.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Specific Mechanisms Ensure Genomic Fidelity within HSCs and upon Aging of HSCs

Abstract: Whether aged hematopoietic stem and progenitor cells (HSPCs) have impaired DNA damage repair is controversial. Using a combination of DNA mutation indicator assays, we observe a 2-3 fold increase in the number of DNA mutations in the hematopoietic system upon aging. Young and aged HSCs and HPCs do not show an increase in mutation upon irradiation-induced DNA damage repair, and young and aged HSPCs respond very similarly to DNA damage with respect to cell cycle checkpoint activation and apoptosis. Both, young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…Finally, novel data from our laboratory demonstrated that the quality of the DDR in HSCs does not change upon aging. HSCs, both young and old, entering cell cycle in vivo upon DNA damage, without initiating a strong G1-S cell cycle arrest as reported for fibroblasts (Moehrle et al 2015). They also do not present with a marked difference in apoptosis in vivo upon induction of DSBs.…”
Section: Dna Damage In Aging Of Hscsmentioning
confidence: 57%
See 2 more Smart Citations
“…Finally, novel data from our laboratory demonstrated that the quality of the DDR in HSCs does not change upon aging. HSCs, both young and old, entering cell cycle in vivo upon DNA damage, without initiating a strong G1-S cell cycle arrest as reported for fibroblasts (Moehrle et al 2015). They also do not present with a marked difference in apoptosis in vivo upon induction of DSBs.…”
Section: Dna Damage In Aging Of Hscsmentioning
confidence: 57%
“…In general though, aged murine hematopoietic cells (either BM or PB, and independent of the type of mutation assay) show a 2–3 fold increase in mutation frequency in hematopoiesis compared to young (Dempsey, Pfeiffer, and Morley 1993; Vijg et al 2005; Moehrle et al 2015), which is also in the range of changes in mutation frequency recently reported for human hematopoietic cells, determined via deep-sequencing approaches (Cancer Genome Atlas Research Network 2013; Welch et al 2012; Genovese et al 2014; Jaiswal et al 2014; McKerrell et al 2015; Xie et al 2014; Papaemmanuil et al 2013). Interestingly, while the overall increase in mutation frequencies in blood cells was found to be again in the range of 2–3 fold, a set of genes including DNMT3A, TET2, JAK2, ASXL1, SF3B1 or SRSF2 were frequently mutated, both in aging associated leukemia but also in aging-associated changes in clonality.…”
Section: Dna Damage In Aging Of Hscsmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, when quiescent, HSCs are not affected by DSBs; however, when prompted to replicate in response to stress, HSCs from aged mice were found to divide more slowly or die (Flach et al, 2014; Moehrle et al, 2015; Rossi et al, 2007; Walter et al, 2015). Indeed, replication stress has been identified as a potent driver of functional decline of old HSCs (Flach et al, 2014).…”
Section: Dsbs Dsb Processing and Agingmentioning
confidence: 99%
“…Secondly, these conclusions were largely based on γH2AX foci formation as a DNA damage ‘marker’ when γH2AX foci are also associated with stalled replication forks and ribosomal biogenesis [44], bringing into question the idea that aged HSCs have more DNA damage than young HSCs. Finally, Moehrle et al recently demonstrated in vivo that aged HSCs repair double-strand breaks as efficiently as young HSCs without accumulating additional DNA mutations [43], data which further question the impact of aging on hematopoietic genetic instability. Consequently, additional studies are warranted to investigate to what extent DDR and impaired genomic integrity impact HSC aging.…”
Section: An Altered Dna Damage Responsementioning
confidence: 99%